The impact of early life maternal deprivation on the perineuronal nets in the prefrontal cortex and hippocampus of young adult rats - Jakovljevic, Ana; Agatonovic, Gorana; Aleksic, Dubravka; Aksic, Milan; Reiss, Gebhard; Förster, Eckart; Stamatakis, Antonios; Jakovcevski, Igor; Poleksic, Joko (Frontiers in Cell and Developmental Biology, 2022)
Early life stress negatively impacts brain development and affects structure and function of parvalbumin immunopositive (PV+) inhibitory neurons. Main regulators of PV+ interneurons activity and plasticity are perineuronal nets (PNNs), an extracellular matrix formation that enwraps PV+ interneurons mainly in the neocortex and hippocampus. To experimentally address the impact of early life stress on the PNNs and PV+ interneurons in the medial prefrontal cortex and dorsal hippocampus in rats, we employed a 24 hours maternal deprivation protocol. We show that maternal deprivation in the medial prefrontal cortex of adult rats caused a decrease in density of overall PNNs and PNNs that enwrap PV+ interneurons in the rostral cingulate cortex. Furthermore, a staining intensity decrease of overall PNNs and PNN+/PV+ cells was found in the prelimbic cortex. Finally, a decrease in both intensity and density of overall PNNs and PNNs surrounding PV+ cells was observed in the infralimbic cortex, together with increase in the intensity of VGAT inhibitory puncta. Surprisingly, maternal deprivation did not cause any changes in the density of PV+ interneurons in the mPFC, neither had it affected PNNs and PV+ interneurons in the hippocampus. Taken together, our findings indicate that PNNs, specifically the ones enwrapping PV+ interneurons in the medial prefrontal cortex, are affected by early life stress.